2015
DOI: 10.1111/jnc.13426
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of myeloperoxidase at the peak of experimental autoimmune encephalomyelitis restores blood–brain barrier integrity and ameliorates disease severity

Abstract: Oxidative stress is thought to contribute to disease pathogenesis in the central nervous system (CNS) disease multiple sclerosis (MS). Myeloperoxidase (MPO), a potent peroxidase that generates toxic radicals and oxidants, is increased in the CNS during MS. However, the exact mechanism whereby MPO drives MS pathology is not known. We addressed this question by inhibiting MPO in mice with experimental autoimmune encephalomyelitis (EAE) using our non-toxic MPO inhibitor KYC. We found that therapeutic administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 76 publications
5
75
0
Order By: Relevance
“…A number of publications have used the Mann Whitney U test (Goldmann et al, 2013; Su et al, 2012; Zhang et al, 2015), the Friedman test (the non-parametric alternative to the one-way ANOVA with repeated measures (all the papers published from our group and others(Du et al, 2011; Hu and Qin, 2013; Spence et al, 2013; Wisdom et al, 2013)), or a two-way ANOVA followed by a Bonferroni post hoc test (Lélu et al, 2010; Rothhammer et al, 2011; Yu et al, 2015) to analyze EAE clinical scores. Unfortunately, multiple issues arise from employing these types of analyses.…”
Section: Discussionmentioning
confidence: 99%
“…A number of publications have used the Mann Whitney U test (Goldmann et al, 2013; Su et al, 2012; Zhang et al, 2015), the Friedman test (the non-parametric alternative to the one-way ANOVA with repeated measures (all the papers published from our group and others(Du et al, 2011; Hu and Qin, 2013; Spence et al, 2013; Wisdom et al, 2013)), or a two-way ANOVA followed by a Bonferroni post hoc test (Lélu et al, 2010; Rothhammer et al, 2011; Yu et al, 2015) to analyze EAE clinical scores. Unfortunately, multiple issues arise from employing these types of analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Using a primary brain microvascular endothelial cell line, it was shown that MPO can directly alter permeability in vitro [120]. In our studies utilizing the novel MPO inhibitor N -acetyl lysyltyrosylcysteine amide (KYC) [121], we found that its daily administration starting at disease initiation did not alter the day of onset or the kinetics of the first seven days of disease progression after which disease progression stalled resulting in a significantly reduced peak and cumulative disease score [122]. These data indicate, that at least in EAE, MPO does not play an essential role in the process of peripheral CD4 T cell priming that is required for EAE onset.…”
Section: Mpo In Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…These data indicate, that at least in EAE, MPO does not play an essential role in the process of peripheral CD4 T cell priming that is required for EAE onset. When KYC was administered therapeutically starting at the peak of disease there was an immediate and significant decrease in disease severity [122]. After only 5 days of KYC treatment there was a significant reduction in the number of macrophages and neutrophils in the CNS [122].…”
Section: Mpo In Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…Using nontoxic inhibition of myeloperoxidase might restore the BBB integrity thereby limiting migration of myeloid cells into the CNS that drive EAE pathogenesis. These inhibitors may be an effective therapeutic agent for the treatment of MS [134]. Yun et al discovered a new molecule with a neuroprotective activity, that is, antioxidant protein peroxiredoxin 6 (PRDX6), which can reduce the inflammation in the CNS and potentiate oligodendrocyte survival [135].…”
Section: The New Possibilities In the Treatment Of Ms: Neuroprotecmentioning
confidence: 99%